Ernst Bloch’s religion without God as an outline of critical philosophy - Pineda Canabal, Aníbal (Estudios de Filosofía, 2020)
One of the most original features of Ernst Bloch’s philosophy is the mixture of religious elements with an emancipation theory rooted in Marxism. However, his philosophy of religion is expressed in an unconventional way. It inherits the best products of the German soul in order to overcome the pessimism of the fin-de-siècle philosophies and revive the emancipatory struggles. This article explores the forms of expression of this thought in Bloch’s early philosophy through the analysis of his claim for “religion without God”, and against all vulgar atheism that abolishes the experience of human inwardness. In this context, the theological concept of the “invisible Church” is presented as Bloch’s way of anchoring the anti-capitalist and anti-militarist struggle in a strong symbolic content that would serve as its base and reserve of energies. The paper concludes that, at the heart of Bloch’s project, there is a radical critique of the economic system and a search for radical alternatives to it.